EFEKTIVITAS MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) KECAMATAN SENAPELAN KOTA PEKANBARU TAHUN 2013 - NAPITUPULU, HOUDSON MARGANDA; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Musrenbang Senapelan Subdistrict is a form of consultative forums or negotiations among stakeholders in a sub-district to discuss and agree on the steps of handling program priority activities listed in the proposed plans for village development activities / village which is integrated with the development priorities of the district / city in the Subdistrict Senapelan. However, sebaimana known, that of every usula development proposed by the community to the government, not all where it can be realized. There is a proposal that should be considered to be realized in the current fiscal year, or be made a priority paa years to come. As the proposal Musrenbang in 2012, of eleven priority proposals, only 4 proposals that can be realized in Senapelan Subdistrict, the city of Pekanbaru.The theory used in this study is the effectiveness of the plan according to Nugroho and Wrihatmolo, who explained that in preparing a plan, there are four things that must be considered, namely the systematic, integrated, Transparency, and Accountability. This study uses qualitative research methods, and assessment data used is data triangulation technique. Where in collecting the data, the authors conducted interviews and observations in the field related to Musrenbang Senapelan District.The results of this study indicate that in the process of planning, has been conducted in accordance with applicable SOP’s Musrenbang Subdistrict, and factors that affect effectiveness of Musrenbang Senapelan Subdistrict include the community, clarity of objectives, indicators of program development, human resource competencies, and budget planning .Keywords: Effectivivness, Planning, Musrenbang